Mesoscopic numerical simulation of chloride diffusion behavior in cracked recycled aggregate concrete - Liu, Jing (Frontiers in Materials, 2024)
The cracking of recycled aggregate concrete (RAC) promotes the chloride diffusion, accelerates the corrosion of reinforcement embedded in RAC. To reveal the mechanism of chloride diffusion in RAC under cracking, a multiphase mesoscopic model for chloride diffusion in RAC was proposed. It should be noted that RAC is regarded as eight-phase composite materials consisting of coarse aggregate, reinforcement, new and old mortar, new and old interface transition zones (ITZ), cracks, and damage zones. The effects of the width and depth of cracks and damage zones on chloride diffusion behavior in RAC after cracking were further investigated. The numerical simulation results show that the damage zones accelerate the chloride diffusion and exacerbates the accumulation effect of chloride at the crack tip. Compared to the crack depth, the crack width of RAC has a small effect on chloride diffusion behavior, especially, the crack width is less than 50 µm. More importantly, the chloride diffusion streamline generated by numerical simulation reveals the mechanism of cracks promoting chloride diffusion. The research in this paper provides new insights into the durability design of RAC by revealing the diffusion behavior of chloride ions in RAC.